Diffusion of Vacancies Created by High‐Energy Heavy Ion Strike Into Diamond. Issue 11 (21st August 2017) - Onoda, Shinobu; Tatsumi, Kazumasa; Haruyama, Moriyoshi; Teraji, Tokuyuki; Isoya, Junichi; Kada, Wataru; Ohshima, Takeshi; Hanaizumi, Osamu
Abstract : A novel technique is proposed to measure how far vacancies diffuse from the initial damaged region with sub‐micrometer resolution. Vacancies created by a single heavy ion with high energy are considered. The most important feature of the single ion track is the quasi‐one‐dimensional vacancy distribution with high volume density, which exceeds 10 19  vacancies cm −3 . After annealing, the vacancies combine with nitrogen impurities to form nitrogen vacancy (NV) centers. With increasing annealing temperature and time, the distribution of NV centers becomes wider. Therefore, the vacancies created by a single heavy ion are suitable to investigate vacancy diffusion. The activation energy of vacancy migration in diamond is determined to be 2.12 eV, which is in reasonable agreement with reported values. Abstract : The migration of vacancy created by a single heavy ion in diamond is studied. After ion irradiation and annealing, the vacancies combine with nitrogen impurities to form nitrogen vacancy (NV) centres. With the increasing annealing temperature and time, the distribution of NV centres becomes wider. The activation energy of vacancy migration in diamond is determined to be 2.12 ev.